Correlation Between Music and Art in Pre-school Institutions - Vojkić, Ljiljana O; Dubljević, Jelena O (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2018)
The results of the research conducted with the aim of examining the influence of music on children´s artistic expression have shown that ”there is a special, almost organic relationship between musical and artistic creative expressions of pre-school children“ (Филиповић, Грујић-Гарић, 2009:319). By correlating the contents of music and art education one can more fully achieve the aims and tasks of pre-school education and upbringing, and children can develop as integral personalities. Pre-school children go through three stages: the scribbling stage /accidental realism - from age 2 to 4/, the preschematic stage /unsuccessful realism - from age 4 to 6/, and the schematic stage /intellectual realism - from age 6 to 9/ (Lovenfeld, 1975, cited in Филиповић, 2011). Likewise, in children´s artistic expression one can notice three levels: intellectual/narrative, artistic/expressive and notional/symbolic, which become even more expressive through musical stimulation (Филиповић, Грујић-Гарић, 2009). A correlation between music and art education in a pre-school institution is mostly based on listening to music which precedes or develops simultaneously with children´s artistic expression. However, playing music can serve as a tool of becoming acquainted with and making difference between colours. Besides, children can become included in designing simple musical instruments (Ђурковић-Пантелић, 1998), or in their modelling with coloured dough or plasticine (Филиповић, Каменов, 2009). The correlation becomes even more conspicuous in musical dramatisation, where it is necessary to decorate the scene and make the costumes. The possibilities of establishing a correlation are numerous and various, and the ways of establishing it are familiar and inciting to children.
Keywords: fine arts; artistic expression; correlation; kindergarden; children; music